Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Chemical constituents of Clerodendrum mandarinorum and their chemotaxonomic significance - Shi-Ya Tian; Feng Li; Huai-Qin Liu; Yu Qiu; Wu-Feng Li; Guang-Yan Liang; Chun-Chun Wang; Xue-Long Yan; Shang-Gao Liao; Qin-Feng Zhu (Biochemical Systematics and Ecology, 2026)

ANGPTL4 in gestational diabetes: a diagnostic biomarker linked to placental senescence - Yu-Feng He; Hui Chen; Chuan-Meng Zhang; Su-Su Yang; Xiao-Long Yang; Li-Shuai Jiang; Fan Wang; Shu-Guang Zhou (Functional & Integrative Genomics, 2026)

Multiscale investigation of lithium and gallium occurrence in coal gangue via combined in situ characterization and density functional theory calculations - Lei Zhang; Yijie Gao; Jinhe Pan; Cheng Liu; Xin He; Xin Long; Mengmeng Shi; Yu Chen; Changchun Zhou; Jinpeng Feng (Minerals Engineering, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Full motion prediction of a free-fall lifeboat under wind loads using a combined time-domain dynamics and CFD method - Feng Xu; Zhi-Dong Wang; Hong-Jie Ling; Yang-Yue Yan; Peng Dou; Yu-Fei Ding; Ji-Ping Yang; Cai-Long Ren (Ocean Engineering, 2026)

Ru-Co bimetallic catalysts with synergistic crystalline phase regulation and hydrogen spillover for deep hydrodeoxygenation of lignin oil - Jing-jing Wu; Jia-yuan Tian; Feng Lin; Yu-long Ma; Yong-gang Sun; Pei Ma; Shuai-lei Li; Xue Zhang; Yi-shu Ma; Xiao-lin Xue (Journal of Environmental Chemical Engineering, 2026)

A biomimetic mineralized injectable hydrogel enables spatiotemporal dual-drug delivery for colorectal cancer therapy - Jing-Yu Feng; Rui Zhang; Jing-Ling Yang; Rui Lu; Kiran Thakur; Fei Hu; Yi-Long Ma; Jian-Guo Zhang; Zhao-Jun Wei (Chemical Engineering Journal, 2026)

Genetic structure and diversity of four Chinese fir breeding populations over 60 years - Qihang Feng; Zhi-Qiang Chen; Benwen Zhao; Long Zhang; Shunde Su; Xie Zhang; Yu Chen; Yousry A. El-Kassaby; Harry X. Wu; Liming Bian (Tree Genetics & Genomes, 2026)

Inoculation with phosphate-solubilizing bacteria reduce the transport of cadmium in Brassica napus L. by reshaping phosphate-solubilizing microbes in rhizosphere - Xiao Chen Zhang; Tong Yu Feng; Xiu Rong Tao; Lu Chen Wang; Jing Wen Kong; Yi Yao Mai; Yang Chen; Qing Guo; Long Guo; Chuan Jun Dai; Min Zhao (Rhizosphere, 2026)

Synthesis of acid-resistant phenanthroline-skeleton polymers applicable to the PUREX process and exploration of their U(VI) adsorption mechanism - Ze-Yang Wang; Wei-Jia Wang; Xin-Long Chen; Xu-Xin Li; Feng Zhang; Ze-Yu Ren; Ze-Yi Yan (Journal of Hazardous Materials, 2026)

Construction of oregano essential oil Pickering emulsions stabilized by Nanocellulose from Xanthoceras sorbifolium shell: Unraveling antibacterial and antioxidant synergy for Agaricus bisporus preservation - Jiayi Du; Yu Huang; Meixi Zhong; Dongmei Li; Yining Chen; Yuanyu Li; Weixia Yang; Long Chen; Xiaoxiao Feng; Yuan Liu; Haiwei Ren (Food Chemistry, 2026)

Unraveling the fruity aroma in soy sauce aroma Baijiu by pinpointing key aroma compounds and evaluating their sensory impact - Yu-Jie Li; Xiao-Juan Zhang; Lan Wu; Zhen-Ming Lu; Lu-Qin Tian; Yun-Hao Lu; Li-Juan Chai; Hong-Yu Xu; Xiao-Long You; Yuan-Long Chi; Feng Hu; Zheng-Hong Xu (Food Chemistry, 2026)

Mitigation role of edible oil and polyol sweeteners in the formation of acrylamide and 5-hydroxymethylfurfural in baked bread - You Long; Feng Li; Yuting Wang; Qiang Yu; Jianhua Xie; Yi Chen (Food Control, 2026)

Effect of arsenic-contaminated irrigation water exposeure combined with conventional and biodegradable microplastics on arsenic fractionation in the paddy soil - Haotian Yu; Fan Wu; Feng Peng; Keyu Long; Yihui Wei; Teng Ma (Environmental Pollution, 2026)

N-vacancy defects engineered MOF/C3N4 based polymeric membrane for H2O2 activation and DOX photo-catalytic degradation in water management - Tian-mi Wang; Ke-yu Long; Cheng-wang Huang; Xu-yao Liu; Hong-jia Yang; Ke-feng Wang; Qing-han Zhou (Chemical Engineering Journal, 2026)

Machine learning-optimized coarse-grained simulations reveal multicomponent solvent-regulated phase separation for precise control of porous polymers - Yun Hao Feng; Bo Zhi Chen; Shi Long Zhang; Chu Qi Wang; Yu Ting He; Yuan Gao; Jing-yi Kang; Ling Liang; Qiang Xu; Bin Du; Xin Dong Guo (Chemical Engineering Journal, 2026)

Dopamine-induced interlayer bridging for enhanced through-plane thermal conductive performance of expanded graphite-based thermal interface materials - Yuyuan Fan; Long Gao; Jinxing Liu; Yajuan Zhong; Sufang Yang; Xueyao Feng; Hongtao Yu; Junfen Li; Xiaodong Tian; Lei Zheng; Xing Guo; Xi Yan; et al. (Chemical Engineering Journal, 2026)

Efficient Preparation of Uniform Saturated Marine Clay via a Combined Vacuum–Capillary Technique - Long Yu; Xingsheng Zhao; Yunrui Han; Li Cheng; Xiaowei Feng; Gang Yang; Qing Yang (Journal of Marine Science and Engineering, 2026)
Model testing is an important method for investigating the interaction between marine structures and soil, and the preparation of high-quality saturated clay samples plays a crucial role in laboratory testing. In this study, a new method for preparing saturated soil samples was developed by combining vacuum extraction and permeation saturation, and its performance was validated through laboratory experiments. A series of laboratory tests, including the gravity and cutting-ring methods, was conducted on columnar soil samples to evaluate the impact of this new technique on soil properties. The results indicate that the soil samples prepared using the new method achieved saturation levels of at least 97% and spatial uniformity. In addition, a large-volume saturated clay sample preparation method was designed and experimentally validated specifically for large-scale model tests. Soil samples were prepared in a model box with dimensions of 300 mm (Lrec) × 300 mm (Wrec) × 200 mm (Drec) in 24–48 h. Both the T-bar penetration and vane shear tests were performed on the prepared soil samples to measure their undrained shear strength. The results show that the middle and lower layers of the large-volume soil samples exhibited spatial uniformity.

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A pulsar escaping an ancient open cluster via tidal stripping - Lei Zhang; Xiaoting Fu; Di Li; Emma Carli; Long Wang; Jiaqi Zhao; Craig O. Heinke; Emanuele Dalessandro; Yang Chen; Angela Bragaglia; Duncan R. Lorimer; Ewan D. Barr; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

FERONIA: Organizing plant thermotolerance from the cell surface - Muhammad Qadir; Shaowen Song; Feng Yu; Long Wang (Molecular Plant, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Beyond pathogens: Emerging contaminant risks following the potomac sewer spill in the United States - Xiaopei Li; Qing Feng; Zhenheng Long; Kunyu Guo; Bin Liu; Peng Gao; Shan Niu; Gang Yu (Journal of Environmental Sciences, 2026)

Screening and identification of soybean antioxidant peptides using Fe3O4-Modified carbon fibers - Xiao-Feng Chen; Xiang-Yu Huang; Hao-Ran Liu; Li Ding; Li Wen; Xu-Feng Wang; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Food Bioscience, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Effects of circumferential and streamwise micro-groove arrangements on the hydrodynamic and acoustic performance of a pump-jet propulsor - Chao Wang; Yu Zhao; Cong Sun; Lian-Zhou Wang; Yu-Long Feng (Ocean Engineering, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Synergistic modulation of electronic structure and surface chemistry in bimetallic MXene for high-performance lithium-ion capacitors - Jinjin Ma; Feng Zhang; Mengzhe Wang; Yajie Hu; Yu Fang; Jianping Long; Yunfeng Guan; Anjun Hu (Chemical Engineering Journal, 2026)

Daphnetin prevents acute graft-versus-host disease by suppressing donor T cell expansion and function - Zhi-Feng Wei; Yan-Fang Chen; Fei Song; Yu Fu; Yun-Wei Zhang; Tian-Xue Qin; Su-Jun Gao; Long Su (Inflammopharmacology, 2026)

Commentary: the TSP-1-CD47-integrin α4β1 axis—deciphering pathogenic mechanisms and therapeutic horizons in rheumatoid arthritis - Jie Guo; Feng-yi Mai; Xin-yu Li; Yu Liu; Jing-rong Liang; Xing-long Li; Chen-guang Li (Inflammation Research, 2026)

Impact of climate change-induced temperature and salinity fluctuations on mussel byssus production and attachment strength - Hai-Long Shen; Hao Lu; Zhe-Yan Chen; Yu-Qing Wang; Ji-Yue Ni; Yi-Feng Li (Marine Environmental Research, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Propyl propionate enabling stable operation of 4.55 V LiCoO2/graphite pouch cells at various temperatures via solvation and interface modulation - Shiran Li; Yu Zhang; Xiao-Zhong Fan; Xiaomeng Wang; Gupei Ding; Weiguo Li; Xu-Feng Zang; Miaomiao Han; Long Kong (Chemical Engineering Journal, 2026)

A state-of-the-art review of accurate and rapid prediction methods for thermal striping phenomenon in nuclear reactors - Mohsin Raza; Ikram UI Haq; Waqar ul Hassan; Jun-Liang Guo; Hong-Na Zhang; Xiao-Bin Li; Yue Wang; Wei-Hua Cai; Shu-Qi Meng; Fang Chen; Yu-Long Mao; Feng-Chen Li (Annals of Nuclear Energy, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Self-assembled 8-shogaol/curcumin nanoparticles via hydrogen bonding: enhanced stability and sustained release in vitro - Rui Zhang; Jing-Yu Feng; Kiran Thakur; Fei Hu; Jian-Guo Zhang; Yi-Long Ma; Zhao-Jun Wei (Food Chemistry, 2026)

Functional role of UGT72B1 in lignin and flavonoid metabolism in Medicago truncatula: Insights from growth, transcriptomic, and metabolomic analyses - Xiangcui Zeng; Andong Yu; Xue Wang; Zhaoming Wang; Jianping Wang; Yarong Zhang; Feng Yuan; Yalin Liu; Junmei Kang; Qingchuan Yang; Jiangqi Wen; Ruicai Long; et al. (Plant Science, 2026)

Ba isotope unmasks recycling processes of fluid mobile elements in subduction zones - Yang Yu; Xiao-Long Huang; Betchaida D. Payot; Hai-Quan Liu; Ying-De Jiang; Yu Wang; Carla B. Dimalanta; Xin-Feng Ou; Gabriel Theophilus V. Valera; Fan Yang; Graciano P. Yumul; Yi-Gang Xu; et al. (Geochimica et Cosmochimica Acta, 2026)

Polyfluoroalkyl substances in aquatic products from Guangdong province, South China: Occurrence, profiles, and health risk assessment - Ximei Wu; Qunjie Feng; Hui Li; Chaoyang Long; Yingxin Yu (Food Control, 2026)

A general framework for designing and assessing sustainable and diversified cropping systems: Bridging knowledge-driven, model-aided, and participatory approaches - Zhengyuan Liang; Bowen Ma; Rui-Peng Yu; Yuewen Huo; Shingirai Mudare; Feiyu Ying; Long Li; Fusuo Zhang; Wen-Feng Cong (Field Crops Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Tracking the dynamic changes in vegetation belts in China: spatiotemporal insights into climate and human influences - Yong Xu; Yun-Gui Lu; Qiang-Yu Dai; Wen-Ting Huang; Shang-Chen Zhou; Ru-Long Ma; Wen-Qiang Peng; Yu-Xi Feng (Regional Environmental Change, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Solvent-mediated construction of phosphate/carboxyl bifunctional hyper-cross-linked polymers for highly efficient uranium removal from aqueous solutions - Ze-Yang Wang; Xin-Long Chen; Xu-Xin Li; Feng Zhang; Wei-Jia Wang; Ze-Yu Ren; Yang Li; Ze-Yi Yan (Journal of Hazardous Materials, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Growth phase-linked Sargassum-associated DOM structures microbial succession and carbon-nutrient coupling in a benthic Sargassum bed - Xiao-Li Ou; Long-Long Huang; Qiu-Jie Wang; Li-Li Xu; Lin-Jian Ou; Yu-Feng Yang (Marine Environmental Research, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Management interventions boost orchid conservation: Evidence from Guizhou, China - Jianghong Yu; Jian Xu; Mingtai An; Guoxiong Hu; Yunli Jiang; Yanbing Yang; Chao Ye; Feng Liu; Xu Wu; Min Long (Biological Conservation, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Seismic performance of precast concrete shear wall with disc spring-bolt subassembly connections - Hua-long LIU; Xun CHONG; Lin-lin XIE; Qing JIANG; Yu-long FENG; Jun-Qi HUANG (Engineering Structures, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Supercritical CO2-assisted pressure homogenization for exfoliating natural graphite toward high-performance graphene cathodes in aluminum-ion batteries - Yue Wu; Jianmin Feng; Li Wang; Jiacheng Qiu; Xuan Song; Xuwang Fu; Ziqi Luo; Jiahan Ma; Xiaoyu Yu; Lei Dong; Yan Han; Conglai Long; et al. (Chemical Engineering Journal, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Harnessing Plant Essential Oils to Combat Acinetobacter baumannii: Research Progress in Antimicrobial Mechanisms and Therapeutic Prospects - Shu-Yun Wei; Yu Sun; Qing Lu; Zhen Liang; Tao Zhu; Yu-Long Li; Ding-Hui Xu; Cai-Ying Li; Feng-Lan Feng; Hong Zeng (Current Microbiology, 2025)

Unlocking ecosystem service potential: Identifying high-sensitivity and high-potential ecological improvement areas in inner Mongolia - Zhen-Zhong Dai; Liang Zou; Xin-Yu Xie; Jia-Jia Duan; Xiao-Long Shi; Zhi-Yuan Zhu; Yong-Zhong Feng; Xing Wang (Journal of Cleaner Production, 2025)

Integration LC-MS/MS and molecular modeling techniques to elucidate the molecular mechanisms of goat whey protein-IgG interactions - Hongbo Li; Quan Gao; Xianjun Gao; Geng Long; Meng Bian; Shuo Feng; Shanbo Mu; Hongjuan Li; Jinghua Yu (Food Chemistry, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Integrating methane conversion with multi-pathway nitrogen removal for wastewater in membrane-enabled stratified biofilm: System development and microbial dynamics - Chun-Yan Yuan; Yu-Xia; Jia-Hao Huo; Cai-Long Nie; Ke-Xin Zhang; Liang-Feng; Xiao-Li Su; Zi Song; Gen-Ping Yi; Fei-Yun Sun (Bioresource Technology, 2025)

Broadening the Na+ diffusion degree of freedom to unlock a rapid sodium storage potential in fluorophosphate cathode - Hong Yu; Jinjin Wang; Hongbo Jing; Chao Wu; Erhai Hu; Shibo Xi; Xiaomei Wang; Zhiyu Fang; Xing-Long Wu; Qinghua Liang; Weihong Qi; Qingyu Yan; et al. (Science Bulletin, 2025)

A two-dimensional discrete metasurface for wireless acoustic communication through water–air interface - Lei Shi; Tong Zhu; Yan-Long Du; Hong-Tao Zhou; Yu-Ze Tian; Yan-Feng Wang; Yue-Sheng Wang (Engineering Structures, 2025)

Regulating electrostatic microenvironments in robust ultramicroporous metal-organic framework for promoting direct ethylene purification from ternary mixtures - Qiang Zhang; Wenxuan Feng; Yi-Long Li; Lan Lan; Yan-Ting Li; Lu-Lu Wang; Xiaolin Yu; Tong-Liang Hu (Chemical Engineering Journal, 2025)

Comparative evaluation of selected adjuvants for possible application of Aeromonas caviae inactivated vaccine in crucian carp (Carassius auratus) - Han Lu; Tao-luo Tao; Yu-Long Liu; Fan Jia; Yi-feng Cui; Xiao-feng Shan (Aquaculture International, 2025)

Precise Prediction and Tiered Mitigation Strategies for Thermal Hazards in Deep Mines: A Data-Driven Approach Applied to Shicaocun Coal Mine - Feng-yuan Lv; Hao-nan Li; Qi-ming Wei; Yan-zi Lei; Long Chen; Yan-bin Yang; Biao Zhao; Yu-liang Sun (Applied Geophysics, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Removal of emerging organic contaminants in a subsurface wastewater infiltration system: A preliminary study of microbial mechanism - Feng-Jiao Peng; Xing-Jun Feng; Sen Li; Xiao-Long Yu; Jun Chen; Shuang-Shuang Liu; Guang-Guo Ying; You-Sheng Liu (Water Research, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Molecular mechanisms underlying multi-generational skeletal abnormalities in marine medaka induced by the quinolone antibiotic norfloxacin (NOR) - Cun-Long Wang; Ping Li; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Multi-omics insights into 6PPD- and 6PPDQ-induced gut-liver axis disruption and non-alcoholic fatty liver disease progression in zebrafish (Danio rerio) - Yu Feng; Hongyi Xian; Ruobing Bai; Zhiming Li; Hao Li; Long Zhang; Xiyun Huang; Yuji Huang; Boxuan Liang; Yanhong Deng; Xiaohong Yang; Xiaoqing Chen; et al. (Journal of Hazardous Materials, 2025)

Ce-modified Ni/SiO2 catalysts via ammonia evaporation method to Regulate nickel phyllosilicate and enhance CO2 methanation performance - Xuemei Wang; Yang Yu; Guangfeng Long; Mingyang Wei; Shafqat Ullah; Tongtong Wang; Hao Deng; Rongbin Zhang; Gang Feng; Runping Ye (Fuel, 2025)

Egg white peptides suppress ghrelin secretion from the stomach by activating the mTOR signaling pathway in rats - Tianliang Wu; Wei Wang; Nan Hai; Ting Cai; Yiju Li; Zhi Feng; Haixi You; Zhipeng Yu; Jingbo Liu; Xuebo Liu; Long Ding (Food Research International, 2025)

Developing multifunctional PtCo/γ-MnO₂@C catalyst for efficient electrocatalytic cleavage of lignin dimers C -O-4 bonds - Yanju Lu; Fengqi Chen; Junming Xu; Jingjing Shi; Feng Long; Yu Zheng; Jiawei Zhang; Shenlin Huang (Chemical Engineering Journal, 2025)

Chitosan/PEO@Eu-MOF nanofiber membrane-based test strip for visual detection of tetracycline with smartphone-assisted analysis - Wei Pan; Zi-Han Zhu; Yan-Shen Zhao; Jie-Liu; Zhi-Guang Zhang; Gui-Xia Li; Tao Yu; Zhong-Zhi Han; Yun-Ze Long; Gui-Feng Yu (Chemical Engineering Journal, 2025)

Host-mediated environmental microbiome recruitment by black soldier fly (Hermetia illucens) enhances waste biotransformation - Zhe Li; Yuchen Zhou; Lin Lv; Yinguang Long; Mengyao Dong; Qi Xiao; Xianyue Jia; Dechen Ju; Xiaowen Sun; Feng Huang; Minmin Cai; Jibin Zhang; et al. (Waste Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

A specific energy and penetration interaction-based method for optimizing TBM operational parameters in hard rock - Lei She; Cheng-cheng Hu; Yan-long Li; Dong-feng Li; Zhao-Yu Li; Tao Fang; Ji-guang Zheng (Tunnelling and Underground Space Technology, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Machine learning-driven molecular generation for accelerated screening of high-performance flame retardants in epoxy resin composites - Zhongwei Chen; Chunlei He; Kai Wang; Feng Rong; Long Xiang; Ziwei Zuo; Changliang Wang; Xinyuan Yang; Yong Guo; Juncheng Jiang; Yuan Yu (Chemical Engineering Journal, 2025)

Preoperative Sleep Deprivation Exacerbates Anesthesia/Surgery-induced Abnormal GABAergic Neurotransmission and Neuronal Damage in the Hippocampus in Aged Mice - Yun Li; Siwen Long; Jiafeng Yu; Jingyu Feng; Shuqi Meng; Yize Li; Lina Zhao; Yonghao Yu (Molecular Neurobiology, 2025)

Re-understanding Sedimentary Characteristics of Shallow-water Delta in Funing Formation, Gaoyou Sag, Subei Basin, Eastern China - Zi-yi Yang; Gui-yu Dong; Lian-bo Zeng; Tian-zhuo Bi; Yong-feng Qiu; Hao Li; Xu Yang; Wen-long Qian; Mehdi Ostadhassan (Applied Geophysics, 2025)

Utilization of UV/VUV irradiation for removal of human body fluids related pollutants in swimming pool water - Dan Li; Liangchen Long; Wei Xia; Weixin Zhao; Likui Feng; Xinhui Xia; Shufei He; Yu Liu; Shijie You; Liangliang Wei (Journal of Hazardous Materials, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Characterization of the thioredoxin peroxidase gene and its role in lambda-cyhalothrin tolerance in Agrotis ipsilon (Lepidoptera: Noctuidae) - Yu Gao; Dong-Yang Liu; Quan Deng; Wen-Long Feng; Jia-Min Yu; Mao-Ye Li; Su Liu (Journal of Asia-Pacific Entomology, 2025)

Milk peptides alleviate irritable bowel syndrome by suppressing colonic mast cell activation and prostaglandin E2 production in mice - Yu Zhang; Zhiqing Lin; Qi Yao; Jian He; Haotian Feng; Wenyi Zhang; Zhigang Liu; Tian Yuan; Xuebo Liu; Long Ding (Food Research International, 2025)

Field tests and structural performance evaluation of existing reinforced concrete hollow slab beam bridges - Jing-Lin Xiao; Yu-Fei Liu; Hao-Long Feng; Jian-Guo Nie (Engineering Structures, 2025)

Interspecific differences in nitrogen form acquisition strategies contribute to species dominance - Ming Guan; Xiao‐Cui Pan; Jian‐Kun Sun; Ji‐Xin Chen; Xiao‐Lin Wei; Bernhard Schmid; Michel Loreau; Yu‐Long Feng (Ecology, 2025)
Plant's ability to use prevalent or less prevalent soil nitrogen (N) forms may affect their dominance within vegetation types, and these partitioning‐driven changes in dominance may facilitate species co‐existence. However, the mechanisms underlying these processes remain unclear, particularly given the strong influence of altitude on soil N forms, which in turn affect plant N acquisition strategy. In this study, we first determined the effects of preference and plasticity in N form uptake on partitioning of soil N forms and species dominance, and then assessed the relative importance of these two N form use strategies for 19 dominant and non‐dominant species in three vegetation types along an altitudinal gradient on Changbai Mountain, northeast China. To achieve this, we measured dominance, the contents of different N forms in rhizosphere soils, their proportional contributions to leaf N, and N form uptake preference and plasticity for these 19 species. Our results show significant interspecific differences in the proportional contributions of different soil N forms to leaf N within all three vegetation types, providing a novel mechanism underlying niche differentiation among plants. Species dominance was positively associated with the proportional contributions of soil dissolved organic N (the most prevalent N form) and the main inorganic N form to leaf N, while negatively with that of the subordinate inorganic N. These associations were not altered by the altitude‐driven changes in the absolute and proportional contents of different soil N forms, suggesting a potentially widespread phenomenon. Both preference and plasticity in N form uptake contributed to the proportional contributions of different N forms to leaf N, and therefore to species dominance and co‐existence within vegetation types. Furthermore, N form preference was more critical for non‐dominant relative to dominant species and at high relative to low altitude, while N form uptake plasticity was more important for dominant species and at low altitude. Our study provides robust evidence for the interspecific niche differentiation in N form uptake, contributing to species dominance and co‐existence within vegetation types, and reveals the mechanisms (plasticity and preference) underlying the association between species dominance and the uptakes of different N forms.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Prediction of landslide dam stability and influencing factors analysis - Zhen-yu Feng; Jia-wen Zhou; Xing-guo Yang; Long-jin Tan; Hai-mei Liao (Engineering Geology, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Construction and application of antimicrobial ultrafiltration membranes based on electro-stimulated hollow mesoporous carbon spheres and carbon nanotubes - Ru-Yu Chang; Wen-Hao Geng; Li-Chao Jing; Jing-Yi Feng; Yue-Xin Wang; Peng-Fei Qian; Ze-Long Bao; Wenyi Wang; Di Zhang; Hong-Zhang Geng (Journal of Environmental Chemical Engineering, 2025)

Out-of-plane performance of BFRP reinforced UHPC thin panel: experiment and numerical analysis - Jun-Qi Huang; Meng Zhao; Dong Guo; Xun Chong; Qing Jiang; Yu-Long Feng (European Journal of Environmental and Civil Engineering, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Nanoparticle-mediated light-driven LAMP combined with test strips for sensitive and rapid visual detection of antibiotic resistance genes - Yu-E. Gao; Qing Huang; Yue Huang; Li-Xia Yan; Wen-Long Wang; WenFeng Zhao; Yong-Wei Feng; Xiao-Dong Huang; Yi Zhang (Journal of Hazardous Materials, 2025)

Performance evaluation of existing reinforced concrete hollow-slab beams: Experiments and fibre beam element-based model updating - Jing-Lin Xiao; Yu-Fei Liu; Hao-Long Feng; Jian-Guo Nie (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Exploring the Correlation Between Varied Serum Iodine Nutritional Levels and Anti-Thyroglobulin Antibodies - Qiuyi Song; Tingting Xu; Yu Wang; Hongyan Wei; Feng Tan; Yanting Chen; Fang Fang; Tingkai Cui; Ziyun Pan; Xiaohui Guo; Wen Chen; Jun Shen; et al. (Biological Trace Element Research, 2025)

Antiplatelet activity and underlying mechanisms of the lophatherum gracile brongn. Extract - Zheng-Yue Yuan; Dong-Mei Yang; Xiao-Yu Hu; Yi-Long Ma; Qian Jiang; Yang Deng; Feng-Wu Qiu (Food Bioscience, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

The role of ferroptosis in acute kidney injury: mechanisms and potential therapeutic targets - Yanxin Yu; Lei Zhang; Die Zhang; Qiangfang Dai; Mingzheng Hou; Meini Chen; Feng Gao; Xiao-Long Liu (Molecular and Cellular Biochemistry, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Dual-ion permeation Janus membrane-assisted element reconstitution system enables fluorosilicate-oriented recovery from fluoride-rich and silica-rich wastewaters - Yangbo Qiu; Chao Wang; Ran Li; Lidong Feng; Shuaijun Yu; Jiangnan Shen; Long-Fei Ren; Jiahui Shao (Water Research, 2025)

Thiolated dextrin nanoparticles for curcumin delivery: Stability, in vitro release, and binding mechanism - Bao Zhang; Shen Long; Ran Feng; Meng-Jie Yu; Bao-Cai Xu; Han Tao (Food Chemistry, 2025)

Stabilizing emulsions by ultrasound-treated pea protein isolate - tannic acid complexes: Impact of ultrasonic power and concentration of complexes on emulsion characteristics - Meng-Jie Yu; Ran Feng; Shen Long; Han Tao; Bao Zhang (Food Chemistry, 2025)

Effects of slurry ice treatment on the physicochemical changes and proteome of large yellow croaker (Larimichthys crocea) - Yan-wei Yuan; Yu-ting Liu; Xing-tong Zhu; Jin-xiu Yu; Jun-long Mao; Jing-jing Fu; Yue-wen Chen; Guo-feng Tan (Food Chemistry, 2025)

Multigenerational effects of combined exposure of triphenyltin and micro/nanoplastics on marine medaka (Oryzias melastigma): From molecular levels to behavioral response - Jian-Xue Feng; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Cun-Long Wang; Ya-Nan Xu; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Novel self-assembled micelles of dual-modified dextrin with pH responsiveness via grafted octenyl succinic anhydride and cysteamine for curcumin delivery - Shen Long; Meng-Jie Yu; Ran Feng; Han Tao; Bao Zhang (Food Chemistry, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Modeling mechanical behavior of buried pipe suffering from frost-heaving force based on the Winkler Elastic Foundation Beam Theory - Xiyan Zhang; Lei Chen; Yu Sheng; Long Huang; Feng Ming; Chenyang Peng (Transportation Geotechnics, 2024)

Arginine alleviates LPS-induced leukocytes inflammation and apoptosis via adjusted NODs signaling - Yuan-Xin Qian; Feng-Feng Zhou; Qiang Chen; Fen Dong; Han-Ying Xu; Yu-Long Sun; Ji-Teng Wang; Tao Han (Fish & Shellfish Immunology, 2024)

Constraining the evaporative loss of zinc during impact processes using terrestrial impact glasses - Zheng-Yu Long; Frédéric Moynier; Marine Paquet; James M.D. Day; Linru Fang; Tu-Han Luu; Dimitri Rigoussen; Kun-Feng Qiu; Jun Deng; Christian Koeberl (Earth and Planetary Science Letters, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Efficient and rapid adsorption of thorium by sp2c-COF with one-dimensional regular micropores channels - Xinyan Li; Zhanjun Zhang; Yaolin Zhao; Long Chen; Chenxi Yu; Xiaojuan Liu; Shangjie Zhao; Zhaoning Feng; Ke Ma; Xiaofan Ding; Jing Zhao; Songtao Xiao (Journal of Environmental Chemical Engineering, 2024)

Species-level understanding of the bacterial community in Daqu based on full-length 16S rRNA gene sequences - Pei-Jie Han; Liang Song; Zhang Wen; Hai-Yan Zhu; Yu-Hua Wei; Jian-Wei Wang; Mei Bai; Lu-Jun Luo; Ju-Wei Wang; Shen-Xi Chen; Xiao-Long You; Da-Yong Han; et al. (Food Microbiology, 2024)

General synthesis of porous metal oxides nanosheets for gas sensing by gradient crystallization induced spatial confinement approach - Xuan-Yu Yang; Rui-Jie Zhao; Fei-Long Gong; Ke-Feng Xie; Hua Xu; Yong-Hui Zhang (Chemical Engineering Journal, 2024)

Deep oxidation of CH2Cl2 over Mo-doped CoAl2O4 spinel oxides: Unravelling the promoting roles of Brønsted acidity and H2O - Yu-Kun Ma; Long-Ren Ouyang; Yi-Fan Yao; Zhi-Feng Dai; Yu Wang; Ji-Qing Lu (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Semi-synthesis and in vitro anti-cancer effects evaluation of novel xanthohumol derivatives - Xiaolong Sun; Jie Chen; Di Huang; Feng Ding; Long Zhao; Hong-Mei Li; Xiang-Shu Wang; Yu-Xin Zhang; Cheng-Zhu Wu (Molecular Diversity, 2024)

Chemical constituents from the aerial parts of Rhododendron thymifolium and its bioactivities against Tribolium castaneum, Lasioderma serricorne, and Ditylenchus destructor - Jun-Yu Liang; Ying-Ying Yang; Rui Feng; Xiao-Han Zhang; Xu-Dong Wang; Jun-Long Wang; Wei-Bao Kong; Ji Zhang (Journal of Plant Diseases and Protection, 2024)

Rock abrasiveness prediction based on multi-source physical, mechanical and mineralogical properties - Yun Wu; Long-Chuan Deng; Xiao-Zhao Li; Li-Yuan Yu; Jiang-Feng Liu; Jian Lin (Bulletin of Engineering Geology and the Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Adolescent co-exposure to environmental cadmium and high-fat diet induces cognitive decline via Larp7 m6A-mediated SIRT6 inhibition - Jin Zhang; Yong-Wei Xiong; Hua-Long Zhu; Lu-Lu Tan; Huan Zhou; Xin-Mei Zheng; Yu-Feng Zhang; Wei Chang; De-Xiang Xu; Tian Wei; Su-Zhen Guan; Hua Wang (Journal of Hazardous Materials, 2024)

LC-MS and GC–MS based metabolomics analysis revealed the impact of tea trichomes on the chemical and flavor characteristics of white tea - Xuyang Liu; Feng Zhou; Mingchun Wen; Shan Jiang; Piaopiao Long; Jia-Ping Ke; Zisheng Han; Mengting Zhu; Yu Zhou; Liang Zhang (Food Research International, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Operating conditions and microbial dynamics transition to sustain integrated anaerobic and aerobic treatment of organic solid wastes for energy and nutrient recovery - Chuanren Qi; Yu Feng; Sumeng Jia; Yangyang Li; Long D Nghiem; Guoxue Li; Wenhai Luo (Chemical Engineering Journal, 2024)

Screening transition metal and nonmetal atoms co-doped graphyne as efficient single-atom catalysts for nitrogen reduction - Shu-Long Li; Ming Peng; Yu Song; Yutao Chen; Liang Qiao; Yong Feng; Yong Zhao; Li-Yong Gan (Chemical Engineering Journal, 2024)

Photothermal flows activated CsPbBr3 ⊆ Pb-TCPP S-scheme heterojunction: In-situ converted interface for robust CO2 reduction coupling with benzylamine oxidation - You-Guo Luo; Cheng-Long Peng; Luo-Bing Tang; Jian-Yong Zhang; Hao-Zhi Wang; Yu-Feng Liu; Qin-Fei Ke; Yong-Zheng Fang; Na Zhang (Chemical Engineering Journal, 2024)

A method for separating tonoplast from wheat - Hui Zhou; Mancang Zhang; Ying Chang; Cuizhu Feng; Yu Long (Journal of Plant Physiology, 2024)

Decrypting the skeletal toxicity of vertebrates caused by environmental pollutants from an evolutionary perspective: From fish to mammals - Cun-Long Wang; Ping Li; Bin Liu; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Environmental Research, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Deficiency of betaine-homocysteine methyltransferase activates glucose-6-phosphate dehydrogenase (G6PD) by decreasing arginine methylation of G6PD in hepatocellular carcinogenesis - Jie Gao; Xiaoyi Shi; Yaohui Sun; Xudong Liu; Feng Zhang; Chengcheng Shi; Xiao Yu; Zhiping Yan; Long Liu; Shizhe Yu; Jiacheng Zhang; Xiaodan Zhang; et al. (Science China Life Sciences, 2024)

Investigation of the mutual crosstalk between ER stress and PI3K/AKT/mTOR signaling pathway in iron overload-induced liver injury in chicks - Xiang-Long Lv; Wen-Lei Li; Feng-Jiao Sun; Yu-Zhi An; Ning Sun; Xiao-Ping Lv; Xue-Li Gao (BioMetals, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Large-scale and facile fabrication of phenyl-containing silicone foam materials with lightweight, wide-temperature flexibility and tunable pore structure for exceptional thermal insulation - Yu-Yue Wu; Zhi-Hao Wu; Zuan-Yu Chen; Li-Dong Peng; Zi-Qi Guan; Yang Li; Cheng-Fei Cao; Guo-Dong Zhang; Jie-Feng Gao; Pingan Song; Yong-Qian Shi; Long-Cheng Tang (Chemical Engineering Journal, 2024)

Taxonomic identification, phenol biodegradation and soil remediation of the strain Rhodococcus sacchari sp. nov. Z13T - Meng Zang; Zhen-Hua Ma; Yu-lei Xu; Xiu-Feng Long (Archives of Microbiology, 2024)

NBR1-dependent autophagy activation protects against environmental cadmium-evoked placental trophoblast senescence - Qing Ling; Yu-Feng Zhang; Wei Chang; Si-Ting Liu; Hua-Long Zhu; Hua Wang (Chemosphere, 2024)

m6A-methylated Lonp1 drives mitochondrial proteostasis stress to induce testicular pyroptosis upon environmental cadmium exposure - Kong-Wen Ouyang; Tian-Tian Wang; Hua Wang; Ye-Xin Luo; Yi-Fan Hu; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Yong-Wei Xiong; Jin Zhang; Wei Chang; Yu-Feng Zhang; et al. (Science of The Total Environment, 2024)

Neoarchean clockwise P-T trajectories with evolution sequence from HP to UHT metamorphism during decompression: Evidence from petrology, mineralogy, and phase equilibria modeling of mafic granulites in the Sittampundi Complex, southern India - Xu Kong; Jun-Sheng Lu; Ming-Guo Zhai; Cheng-Li Zhang; M.P. George; Long-Long Gou; Yan Zhao; Wen-Hao Ao; Yu-Hua Hu; Qiang Feng; Gang Liu (Precambrian Research, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Locally released H2 and O2 from an artificial periosteum modulate the survival and reparative activities of stem cells derived from the aged human nasal mucosa after transplantation - Wentao Shi; Sainan Chen; Xuan Zhang; Lu Bian; Mengyuan Yu; Jun Wang; Suyin Feng; Long Lv; Yunduan Que; Hong Tang; Qing Wang; Xuechao Wu; et al. (Chemical Engineering Journal, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Morphological characteristics, genetic diversity, and ethnobotanical uses of Citrus hongheensis (Rutaceae), an endangered species - Feng-Juan Mou; Jian-Qin Li; Yu-Hong Gao; Yue-Yan Li; Ting-Yao Meng; Shun-Long Han (Plant Biosystems, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Spatiotemporal variations, sources, and atmospheric transformation potential of volatile organic compounds in an industrial zone based on high-resolution measurements in three plants - Jin-Long Mai; Xing-Cong Cai; De-Yao Luo; Yuan Zeng; Yu-Feng Guan; Wei Gao; She-Jun Chen (Science of The Total Environment, 2024)

Studies on the mechanism of the contact toxicity of carvone against Tribolium castaneum - Jun-Yu Liang; Zhi-Bo Hou; Xiao-Han Zhang; Qian Zhang; Zhen-jia Ma; Wei-Bao Kong; Jun-Long Wang; Ji Zhang; Feng Zhou (Journal of Stored Products Research, 2024)

Environmental cadmium inhibits testicular testosterone synthesis via Parkin-dependent MFN1 degradation - Tian-Tian Wang; Hua-Long Zhu; Kong-Wen Ouyang; Hua Wang; Ye-Xin Luo; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Jin Zhang; Wei Chang; Qi Lu; Yu-Feng Zhang; et al. (Journal of Hazardous Materials, 2024)

Maternal prednisone exposure during pregnancy elevates susceptibility to osteoporosis in female offspring: The role of mitophagy/FNDC5 alteration in skeletal muscle - Zun-Yu Du; Hua-Long Zhu; Wei Chang; Yu-Feng Zhang; Qing Ling; Kai-Wen Wang; Jin Zhang; Quan-Bing Zhang; Xiu-Li Kan; Qu-Nan Wang; Hua Wang; Yun Zhou (Journal of Hazardous Materials, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Prussian blue analogue nanospheres immobilized on self-floating biochar for micropollutant degradation via photo-Fenton process - Fu-Xue Wang; Zi-Wei Zhang; Zi-Chen Zhang; Ke-Xin Li; Ya Li; Hong-Yu Chu; Chong-Chen Wang; Jian-Feng Wang; Long Chen; Wen Liu; Hailong Wang; Peng Wang (Chemical Engineering Journal, 2024)

Social parasitism behavior between two species of edible wasps in China - Cheng-Ye Wang; Hao-Yu Chen; Bing-Qing Fang; Pan-Li Yang; Zhao He; Long Sun; Jin Gan; Min Zhao; Ying Feng (Journal of Ethology, 2024)

Curation, nomenclature, and topological classification of receptor-like kinases from 528 plant species for novel domain discovery and functional inference - Qian Liu; Qiong Fu; Yujie Yan; Qian Jiang; Longfei Mao; Long Wang; Feng Yu; Heping Zheng (Molecular Plant, 2024)

Exploring correlations between soy sauce components and the formation of thermal contaminants during low-salt solid-state fermentation - Feng Li; Yuting Wang; Hongxia Liao; You Long; Qiang Yu; Jianhua Xie; Yi Chen (Food Research International, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

Progress of 3-ketosteroid Δ1-dehydrogenases for steroid production - Bo Zhang; Deng-Feng Zhou; Meng-Juan Li; Jia-Hui Lan; Hui Li; Ming-Long Shao; Zhi-Qiang Liu; Yu-Guo Zheng (Systems Microbiology and Biomanufacturing, 2024)

Phase separation of GRP7 facilitated by FERONIA-mediated phosphorylation inhibits mRNA translation to modulate plant temperature resilience - Fan Xu; Long Wang; Yingbin Li; Junfeng Shi; Dorothee Staiger; Feng Yu (Molecular Plant, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Potassium isotopes as a tracer of hydrothermal alteration in ore systems - Kun-Feng Qiu; Rolf L. Romer; Zheng-Yu Long; Hao-Cheng Yu; Simon Turner; Ruo-Qi Wan; Xiao-Qiang Li; Zi-Yue Gao; Jun Deng (Geochimica et Cosmochimica Acta, 2024)

The effect of the mitochondria-targeted antioxidant Mito-tempo during sperm ultra-rapid freezing - Chun-Yuan Li; Juan Liu; Qi-Yuan Zheng; Nian Liu; Xi-Ling Huang; Yu-Yin Wu; Xing-Feng Yao; Qing-Ying Tan; Ying Huang; Chuan-Huo Hu; Chang-Long Xu (Cryobiology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Temporal dynamics of plant−soil feedback and related mechanisms depend on environmental context during invasion processes of a subtropical invader - Yang-Ping Li; Wei-Tao Li; Ju Li; Yu-Long Feng (Plant and Soil, 2024)

Distribution of gasification products and emission of heavy metals and dioxins from municipal solid waste at the low temperature pyrolysis stage - Shi Feng; Yu-Han Feng; Long-jie Ji; Ming-Xiu Zhan; Jin-Qing Wang; Xu Xu (Environmental Science and Pollution Research, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Long-term tralopyril exposure results in endocrinological and transgenerational toxicity: A two-generation study of marine medaka (Oryzias melastigma) - Bin Liu; Ping Li; Ren-Yan Du; Cun-Long Wang; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Ti3C2Tx quantum dot-modified Ti3C2Tx nanosheets freestanding films for flexible solid-state pseudocapacitors - Ping Liu; Handan Liu; Tengfei Zhang; Long Chen; Wen Guo; Tiantian Gu; Feng Yu; Yanyan Liu; Gang Wang (Chemical Engineering Journal, 2023)

Amino-carboxyl cellulose for adsorption of Cd2+ and Pb2+ - Jin Gou; Wen Zhang; Xiao-Feng Wang; Dong Hao; Hua Shen; Nan You; Wen-Yu Long (Chemosphere, 2023)

Corrigendum to “Ca2+ plays an antiviral role by increasing p53 expression to achieve protection against spring viraemia of carp virus infection” [Fish Shellfish Immunol. 102 (2020) 449–459/455] - Long-Feng Lu; Xiao-Yu Zhou; Can Zhang; Zhuo-Cong Li; Dan-Dan Chen; Yong-An Zhang; Shun Li (Fish & Shellfish Immunology, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Aflatoxin B1 affects porcine alveolar macrophage growth through the calcium signaling pathway mediated by the ceRNA regulatory network - Yu Tian; Pei-Yu Dong; Sheng-Lin Liang; Long Li; Shu-Er Zhang; Francesca Gioia Klinger; Wei Shen; You-Yu Yan; Xi-Feng Zhang (Molecular Biology Reports, 2023)

Chemical constituents of Aspergillus udagawae isolated from the soil of the Xingren coal areas and their antibacterial activities - Xing-Mei Long; Qin-Feng Zhu; Bing Wang; Guang-Gui Chen; Kai-Yu Li; Xun He; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2023)

Sperm Rhoa m6A modification mediates intergenerational transmission of paternally acquired hippocampal neuronal senescence and cognitive deficits after combined exposure to environmental cadmium and high-fat diet in mice - Jin Zhang; Yong-Wei Xiong; Lu-Lu Tan; Xin-Mei Zheng; Yu-Feng Zhang; Qing Ling; Chao Zhang; Hua-Long Zhu; Wei Chang; Hua Wang (Journal of Hazardous Materials, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Loss of Atg5 in Sertoli cells enhances the susceptibility of cadmium-impaired testicular spermatogenesis in mice - Yong-Wei Xiong; Dai-Xin Li; Zheng-Jia Ling; Lu-Lu Tan; Yu-Feng Zhang; Jin Zhang; Hao Li; Wei Chang; Hua-Long Zhu; Jun Zhang; Lan Gao; De-Xiang Xu; et al. (Food and Chemical Toxicology, 2023)

Molecular bases for the stronger plastic response to high nitrate in the invasive plant Xanthium strumarium compared with its native congener - Chang Zhang; Shi-Ting Wang; Jian-Zhi Li; Yu-Long Feng (Planta, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Metamorphic P–T evolution of the pelitic granulites from the Helanshan in the North China Craton revealed by phase equilibrium modeling and garnet trace elements: Implications for Paleoproterozoic collisional orogenesis - Xiao-Fei Xu; Long-Long Gou; Yun-Peng Dong; Cheng-Li Zhang; Xiao-Ping Long; Yu-Hang Zhao; Feng Zhou; Zhi-Bo Tian (Precambrian Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Co-pyrolysis of dyeing sludge and pine sawdust in a fluidized bed: Characterization and analysis of pyrolytic products and investigation of synergetic effects - Bang Yao; Xiangtong Li; Chunbao Zhou; Feng Lv; Changfa Zhang; Long Wang; Mengyan Yu; Yanxin Yuan; Yingwen Zhang; Yajie Jin; Yang Liu; Jianjun Dai (Waste Management, 2023)

Contamination characteristics and source analysis of potentially toxic elements in dustfall-soil-crop systems near non-ferrous mining areas of Yunnan, southwestern China - Ying Luo; Zhe Wang; Zhen-Long Zhang; Jia-Qian Zhang; Qiu-Ping Zeng; Duan Tian; Chao Li; Feng-Yu Huang; Shu Chen; Li Chen (Science of The Total Environment, 2023)

An online intelligent management method for wastewater treatment supported by coupling data-driven and mechanism models - Jian-Hui Wang; Du-Jiang Zhao; Wan-Shan Liao; Mohamed S. Mahmoud; Zhi-Wei Guo; Hui-Min Li; Xu Gao; Dong Feng; Long-Fei Shi; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2023)

Activation of Atg5-dependent placental lipophagy ameliorates cadmium-induced fetal growth restriction - Yu-Feng Zhang; Hua-Long Zhu; Xiao-Feng Xu; Jin Zhang; Qing Ling; Shuang Zhang; Wei Chang; Yong-Wei Xiong; De-Xiang Xu; Hua Wang (Environmental Pollution, 2023)

Experimental analysis of the height–diameter ratio effect of rock energy under uniaxial cyclic loading–unloading conditions - Qing-bin Meng; Jiang-feng Liu; Bing-xiang Huang; Zhi-zhen Zhang; Jing-kui Long; Jiang-yu Wu (Bulletin of Engineering Geology and the Environment, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Chloroacetonitrile exposure induces endoplasmic reticulum stress and affects spindle assembly in mouse oocytes - Feng-Xin Qiao; Ming-Xin Sun; Zhi-Ran Xu; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

A simple and efficient protocol for transient transformation of sliced grape berries - Mao-Song Pei; Hai-Nan Liu; Charles Ampomah-Dwamena; Tong-Lu Wei; Yi-He Yu; Jia-Bing Jiao; Ying-Ying Lv; Feng Li; Hong-Chao Li; Xue-Jie Zhu; Da-Long Guo (Protoplasma, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Rayleigh surface wave inversion based on an improved Archimedes optimization algorithm - Zhen-An Yao; Ren Wang; Fu Yu; Long-Feng Chen; Hong-Xing Li; Xiang-Teng Wang; Pan Wang (Applied Geophysics, 2023)

Optimization of natural deep eutectic solvents extraction of flavonoids from Xanthoceras sorbifolia Bunge by response surface methodology - Zhi-ao Feng; Dan Yang; Jin-jin Guo; Yu-kun Bo; Long-shan Zhao; Ming An (Sustainable Chemistry and Pharmacy, 2023)

Localized photo-Fenton reaction boosted by spontaneous generation of H2O2 from thin water membrane - Juan Li; Yu Xia; Jingxing Li; Kaixiang Long; Fengjie Chen; Min Feng; ShiShang Guo; Bolei Chen (Journal of Water Process Engineering, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Anti-neuroinflammatory sesquiterpenoids from Chloranthus henryi - Xue-Jiao Wang; Jun-Li Xin; Sheng-Zhou Yu; Li-Long Pan; Jin-Feng Hu; Juan Xiong (Natural Product Research, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Deployment optimization of battery swapping stations accounting for taxis’ dynamic energy demand - Tian-yu Zhang; En-jian Yao; Yang Yang; Long Pan; Cui-ping Li; Bin Li; Feng Zhao (Transportation Research Part D: Transport and Environment, 2023)

Cobalt chloride exposure disturbs spindle assembly and decreases mouse oocyte development potential - Si-Cheng Zhao; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhi-Ran Xu; Yu Liu (Toxicology, 2023)

Short-term application of organic fertilization impacts phosphatase activity and phosphorus-mineralizing bacterial communities of bulk and rhizosphere soils of maize in acidic soil - Long Guo; Chao Wang; Tong Yu Feng; Ren Fang Shen (Plant and Soil, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

Giant Mesozoic gold ores derived from subducted oceanic slab and overlying sediments - Kun-Feng Qiu; Jun Deng; Crystal Laflamme; Zheng-Yu Long; Ruo-Qi Wan; Frederic Moynier; Hao-Cheng Yu; Jing-Yuan Zhang; Zheng-Jiang Ding; Richard Goldfarb (Geochimica et Cosmochimica Acta, 2023)

Age, formation mechanisms, spatial extent, and geodynamic effects of the eastern and northeastern Asian big mantle wedges - Jie Tang; Feng Wang; Yi-Ni Wang; Xin-Yu Long; Wen-Liang Xu (Earth-Science Reviews, 2023)

Development and application of a multiplex qPCR assay for the detection of duck circovirus, duck Tembusu virus, Muscovy duck reovirus, and new duck reovirus - Yan Wen Yin; Chenyong Xiong; Kai Chuang Shi; Shou Yu Xie; Feng Long; Jun Li; Min Zheng; Xian Kai Wei; Shuping Feng; Sujie Qu; Wenjun Lu; Hongjin Zhou; et al. (Virus Genes, 2023)

Triptolide exposure induces oxidative stress and decreases oocyte quality in mouse - Qian-Qian Hao; Zhi-Ran Xu; Han Nie; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Toxicon, 2023)

Phylogeny, character evolution, and biogeography of the fern genus Bolbitis (Dryopteridaceae) - Li-Yun Nie; Liang Zhang; Zhen-Long Liang; Rossarin Pollawatn; Yue-Hong Yan; Ngan Thi Lu; Ralf Knapp; Xia Wan; Daniele Cicuzza; Xin-Xin Cheng; Hong-Feng Chen; Ai-Hua Wang; et al. (Molecular Phylogenetics and Evolution, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Efficient microalgal lipid production driven by salt stress and phytohormones synergistically - Zi-Yan Yang; Kai-Xuan Huang; Yu-Ru Zhang; Lei Yang; Jin-Long Zhou; Qiao Yang; Feng Gao (Bioresource Technology, 2023)

Characteristics and source analysis of potentially toxic elements pollution in atmospheric fallout around non-ferrous metal smelting slag sites—taking southwest China as an example - Ying Luo; Zhe Wang; Zhen-Long Zhang; Feng-Yu Huang; Wen-Jing Jia; Jia-Qian Zhang; Xi-Yang Feng (Environmental Science and Pollution Research, 2023)

Antibacterial activities of the chemical constituents of Schizophyllum commune MST7-3 collected from coal area - Guang-Gui Chen; Qin-Feng Zhu; Xing-Mei Long; Qian Lu; Kai-Yu Li; Qian Chen; Meng Zhou; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2022)

Genome-wide association study reveals a NAC transcription factor TaNAC074 linked to pre-harvest sprouting tolerance in wheat - Hao Jiang; Yu Fang; Dong Yan; Si-tong Liu; Jun Wei; Fei-long Guo; Xing-ting Wu; Hong Cao; Chang-bin Yin; Fei Lu; Li-feng Gao; Yong-xiu Liu (Theoretical and Applied Genetics, 2022)

Potential antibacterial and anti-biofilm effects of Anoectochilus roxburghii rhizome cultures - Ming-Zhi Fan; Xiao-Long Jiang; Xuan-Chun Piao; Xue-Feng Li; Mei-Yu Jin; Mei-Lan Lian (Journal of Plant Biochemistry and Biotechnology, 2022)

Trophinin-associated protein expression correlates with shorter survival of patients with glioma: a study based on multiple data fusion analysis - Yong Sun; Zhen Dong Liu; Run Ze Liu; Xiao Yu Lian; Xing Bo Cheng; Yu Long Jia; Bin Feng Liu; Yan Zheng Gao; Xinjun Wang (Molecular Biology Reports, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Assessment of heavy metals in surface water, sediment and macrozoobenthos in inland rivers: a case study of the Heihe River, Northwest China - Yu Wang; Bao-long Li; Jia-le Zhu; Qi Feng; Wei Liu; Yu-hua He; Xu Wang (Environmental Science and Pollution Research, 2022)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Expansion of bilin‐based red light sensors in the subaerial desert cyanobacterium Nostoc flagelliforme - Hai‐Feng Xu; Guo‐Zheng Dai; Yu‐Jie Wang; Chao Cheng; Jin‐Long Shang; Ren‐Han Li; Ke Liu; Deqiang Duanmu; Bao‐Sheng Qiu (Environmental Microbiology, 2022)
Summary Light is the crucial environmental signal for desiccation‐tolerant cyanobacteria to activate photosynthesis and prepare for desiccation at dawn. However, the photobiological characteristics of desert cyanobacteria adaptation to one of the harshest habitats on Earth remain unresolved. In this study, we surveyed the genome of a subaerial desert cyanobacterium Nostoc flagelliforme and identified two phytochromes and seven cyanobacteriochromes (CBCRs) with one or more bilin‐binding GAF (cGMP phosphodiesterase/adenylyl cyclase/FhlA) domains. Biochemical and spectroscopic analyses of 69 purified GAF‐containing proteins from recombinant phycocyanobilin (PCB), biliverdin or phycoerythrobilin‐producing Escherichia coli indicated that nine of these proteins bind chromophores. Further investigation revealed that 11 GAFs form covalent adducts responsive to near‐UV and visible light: eight GAFs contained PCB chromophores, three GAFs contained biliverdin chromophores and one contained the PCB isomer, phycoviolobilin. Interestingly, COO91_03972 is the first‐ever reported GAF‐only CBCR capable of sensing five wavelengths of light. Bioinformatics and biochemical analyses revealed that residue P132 of COO91_03972 is essential for chromophore binding to dual‐cysteine CBCRs. Furthermore, the complement of N . flagelliforme CBCRs is enriched in red light sensors. We hypothesize that these sensors are critical for the acclimatization of N . flagelliforme to weak light environments at dawn.

Diketopiperazine and enterotoxin analogues from the mangrove derived-soil Streptomyces sp. SCSIO 41400 and their biological evaluation - Meng-Meng Song; Yu-Hui Xie; Wei-Hao Chen; Yi-Wei Hu; Kai Zhao; Yong-Hong Liu; Xiao-Long Huang; Qing-Chao Liu; Jun-Feng Wang (Natural Product Research, 2022)

Inherent conflicts between reaction norm slope and plasticity indices when comparing plasticity: a conceptual framework and empirical test - Shuo Wang; Wei-Wei Feng; Ming-Chao Liu; Kai Huang; Pieter A. Arnold; Adrienne B. Nicotra; Yu-Long Feng (Oecologia, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Effects of cascade reservoir systems on the longitudinal distribution of sediment characteristics: a case study of the Heihe River Basin - Yu Wang; Bao-long Li; Juan-juan Liu; Qi Feng; Wei Liu; Xu Wang; Yu-hua He (Environmental Science and Pollution Research, 2022)
Spatial variations in grain size parameters can reflect river sediment transport patterns and depositional dynamics. Therefore, 22 surficial sediment samples taken from the Heihe River and its cascade reservoirs were analyzed to better understand the impact of cascade reservoir construction on sediment transport patterns in inland rivers in China. The results showed that the longitudinal distribution of sediment grain size in the Heihe River was significantly affected by the influence of the cascade reservoirs. The retention rate in the cascade reservoir of the Heihe River reached 79% (193.53 Mt/year), which caused most of the fine sand to accumulate in the reservoir, and the sediment fining degree reached approximately 50%. However, the water discharged from the dam caused serious erosion of the riverbed and coarsening of the sediment, and the coarsening degree was approximately 500%. The backwater zone of the reservoir was influenced by both backwater and released water, and the coarsening degree of sediment was approximately 101%. Sedimentary environmental analysis revealed that the characteristics of the sediment grain size in an upstream tributary of the Heihe River were more influenced by source material than by hydrodynamic conditions, while the grain size characteristics of the mainstream sediments were controlled mainly by hydrodynamic conditions. The characteristics of sediment transport in different reaches of the Heihe River were studied, and the results may provide references for the operation of cascade reservoirs and the sediment control of reservoirs.

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Refractory organic compounds in coal chemical wastewater treatment by catalytic ozonation using Mn-Cu-Ce/Al2O3 - Kang-He Zhao; Yu-Long Ma; Feng Lin; Shao-Ying Ge; Li Zhu (Environmental Science and Pollution Research, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Causes and treatment measures for deformation of retaining soil and slope - Yu Liang; Wei Long; Peidong Su; Feng Yang (Arabian Journal of Geosciences, 2021)

Chemical constituents from Jasminum pentaneurum Hand.-Mazz and their cytotoxicity against human cancer cell lines - Wei Wei; Er-Wei Hao; Meng Zhang; Xiang-Long Pan; Jian-Feng Qin; Jin-Ling Xie; Jiang-Yu Zhou; Xiao-Tao Hou; Jia-Gang Deng (Natural Product Research, 2021)

Development of ecosystem carbon stock with the progression of a natural mangrove forest in Yingluo Bay, China - Chenxi Yu; Dongsheng Guan; Wang Gang; Duo Lou; Long Wei; Yi Zhou; Jianxiang Feng (Plant and Soil, 2021)

Irrigation and fertilization management to optimize rice yield, water productivity and nitrogen recovery efficiency - Xiao-chuang Cao; Long-long Wu; Ruo-hui Lu; Lian-feng Zhu; Jun-hua Zhang; Qian-yu Jin (Irrigation Science, 2021)

Roles of FERONIA-like receptor genes in regulating grain size and quality in rice - Long Wang; Dandan Wang; Zhuhong Yang; Shun Jiang; Jianing Qu; Wei He; Zhenming Liu; Junjie Xing; Youchu Ma; Qinlu Lin; Feng Yu (Science China Life Sciences, 2021)

Phosphate recovery and simultaneous nitrogen removal from urine by electrochemically induced struvite precipitation - Xin Tan; Rongtai Yu; Gang Yang; Feng Wei; Lulu Long; Fei Shen; Jun Wu; Yanzong Zhang (Environmental Science and Pollution Research, 2021)

Spatial variation in macrobenthic assemblages and their relationship with environmental factors in the upstream and midstream regions of the Heihe River Basin, China - Yu Wang; Juan-Juan Liu; Wei Liu; Qi Feng; Bao-long Li; Han Lu; Shuang Wang (Environmental Monitoring and Assessment, 2021)
The Heihe River is a typical inland river under increasing anthropogenic pressure. To explore the characteristics of the macrobenthic assemblages and their relationships with environmental factors in the upstream and midstream regions of this basin, abiotic conditions and macrobenthic assemblages were investigated in the summers of 2018 and 2019. A total of 50 species were collected, and Arthropoda and mollusks were the dominant groups. A significant increase in standing stock was observed from the upstream to midstream, and predators (PR) were the main functional feeding group. A one-way analysis of variance (ANOVA) revealed that the Shannon-Wiener index and Margalef’s index values significantly differed at the spatial scale ( P < 0.05). A redundancy analysis (RDA) and Pearson correlation analysis showed that the spatial heterogeneity of the macrobenthos was influenced by the biochemical oxygen demand (BOD 5 ), water temperature (WT), total nitrogen (TN), salinity, electrical conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), and potassium permanganate index (COD Mn ) ( P < 0.05). The spatial variation of macrobenthos was mainly governed by natural conditions and human disturbances.

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

TNFSF13 upregulation confers chemotherapeutic resistance via triggering autophagy initiation in triple-negative breast cancer - Hui-Yu Lin; Chia-Hao Kuei; Hsun-Hua Lee; Che-Hsuan Lin; Yen-Lin Chen; Chi-Long Chen; Yuan-Feng Lin (Journal of Molecular Medicine, 2020)

First record of field dodder (Cuscuta campestris) parasitizing invasive buffalobur (Solanum rostratum) - Wei-Bin Wang; Fan-Fan Gao; Mei-Ni Shao; Ming-Chao Liu; Hong-Feng Zhai; Bo Qu; Yu-Long Feng (Journal of Plant Pathology, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Evaluation of the Biodiversity Conservation Function in Liaohe Delta Wetland, Northeastern China - Wenying Yu; Ruipeng Ji; Xiuzhen Han; Long Chen; Rui Feng; Jinwen Wu; Yushu Zhang (Journal of Meteorological Research, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Nitric Oxide Negatively Regulates Larval Metamorphosis in Hard-Shelled Mussel (Mytilus coruscus) - You-Ting Zhu; Ya Zhang; Yu-Zhu Liu; Yi-Feng Li; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang; Xiao Liang (Frontiers in Marine Science, 2020)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Widespread Os-isotopically ultradepleted mantle domains in the Paleo-Asian oceanic upper mantle: evidence from the Paleozoic Tianshan ophiolites (NW China) - Xiao-Han Gong; Ji-Feng Xu; Xi-Jun Liu; Xiao-Xiao Huang; Zhi-Guo Zhang; Hai-Long Zhou; Zheng-Yu Yang; Wen-Xia Zhao (International Journal of Earth Sciences, 2020)

Potent antitumor activity of oncolytic adenovirus expressing C/EBPβ against hepatocellular carcinoma - Yan Zeng; Feng-di Li; Jiang-long Du; Yu-jia Xue; Jing Liu; Xin Cao; Hai-zhen Wang (Apoptosis, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

Founder effects, post-introduction evolution and phenotypic plasticity contribute to invasion success of a genetically impoverished invader - Zhi-Yong Liao; J. F. Scheepens; Qiao-Ming Li; Wei-Bin Wang; Yu-Long Feng; Yu-Long Zheng (Oecologia, 2020)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Quantitative Evaluation Methods of Brittle Failure Characteristics of Coal: A Case Study of Hard Coal in China - Bo Ren; Shao-hua Wang; Jun-hua Xue; Kai-long Qiu; Guo-feng Yu; Ying-jie Fan; Shi-qi Zhao; Zhen-yu Du; Dong-sheng Deng; Xian-jie Hao (Geotechnical and Geological Engineering, 2019)

Variations in dissolved inorganic carbon species in effluents from large-scale municipal wastewater treatment plants (Qingdao, China) and their potential impacts on coastal acidification - Xiang-Yu Liu; Xu-Feng Yang; Yun-Xiao Li; Han Zang; Long-Jun Zhang (Environmental Science and Pollution Research, 2019)

Genetic characterization of a novel G9P[23] rotavirus A strain identified in southwestern China with evidence of a reassortment event between human and porcine strains - Danyu Chen; Long Zhou; Yiming Tian; Xuan Wu; Lan Feng; Xiping Zhang; Zhihui Liu; Shurui Pang; Runmin Kang; Jifeng Yu; Yonggang Ye; Hongning Wang; et al. (Archives of Virology, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Garnet amphibolites from the Ganzi–Litang fault zone, eastern Tibetan Plateau: mineralogy, geochemistry, and implications for evolution of the eastern Palaeo-Tethys Realm - Qiu-Huan Li; Yu-Xiu Zhang; Kai-Jun Zhang; Li-Long Yan; Lu Zeng; Xin Jin; Jin-Feng Sun; Xiao-Yao Zhou; Xian-Chun Tang; Lu Lu (International Geology Review, 2018)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

Morphology and multigene phylogeny reveal new genus and species of Torulaceae from freshwater habitats in northwestern Yunnan, China - Xi-Jun Su; Zong-Long Luo; Rajesh Jeewon; Darbhe J. Bhat; Dan-Feng Bao; Wen-Li Li; Yu-E Hao; Hong-Yan Su; Kevin D. Hyde (Mycological Progress, 2018)

PGL3 is required for chlorophyll synthesis and impacts leaf senescence in rice - Jing Ye; Yao-long Yang; Xing-hua Wei; Xiao-jun Niu; Shan Wang; Qun Xu; Xiao-ping Yuan; Han-yong Yu; Yi-ping Wang; Yue Feng; Shu Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Geochronology and geochemistry of Early Devonian intrusions in the Qimantagh area, Northwest China: evidence for post-collisional slab break-off - Jing Chen; Bing-zhang Wang; Hai-feng Lu; Bin Li; Ji-qing Li; Yu-long Li; Shu-lan Shu (International Geology Review, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

Subchondral mesenchymal stem cells from osteoarthritic knees display high osteogenic differentiation capacity through microRNA-29a regulation of HDAC4 - Wei-Shiung Lian; Ren-Wen Wu; Mel S. Lee; Yu-Shan Chen; Yi-Chih Sun; Shing-Long Wu; Huei-Jing Ke; Jih-Yang Ko; Feng-Sheng Wang (Journal of Molecular Medicine, 2017)

Changes by cadmium stress in lipid peroxidation and activities of lipoxygenase and antioxidant enzymes in Arabidopsis are associated with extracellular ATP - Qin-zheng Hou; Guang-ji Ye; Rong-fang Wang; Ling-yun Jia; Jun-yu Liang; Han-qing Feng; Jing Wen; Dai-long Shi; Qing-wen Wang (Biologia, 2017)

Anti-complementary constituents of Anchusa italica - Yu-zhen Hou; Kui-kui Chen; Xi-ling Deng; Ze-long Fu; Dao-feng Chen; Qi Wang (Natural Product Research, 2017)

Applying a Ruggiero three-stage super-efficiency DEA model to gauge regional carbon emission efficiency: evidence from China - Feng Dong; Ruyin Long; Zhengfu Bian; Xihui Xu; Bolin Yu; Ying Wang (Natural Hazards, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Histone demethylase UTX counteracts glucocorticoid deregulation of osteogenesis by modulating histone-dependent and -independent pathways - Feng-Sheng Wang; Wei-Shiung Lian; Mel S. Lee; Wen-Tsan Weng; Ying-Hsien Huang; Yu-Shan Chen; Yi-Chih Sun; Shing-Long Wu; Pei-Chin Chuang; Jih-Yang Ko (Journal of Molecular Medicine, 2017)

Koumine exhibits anxiolytic properties without inducing adverse neurological effects on functional observation battery, open-field and Vogel conflict tests in rodents - Chao-Jie Chen; Zhi-Feng Zhong; Zhi-Ming Xin; Long-Hui Hong; Yan-Ping Su; Chang-Xi Yu (Journal of Natural Medicines, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Integrative analysis for identification of shared markers from various functional cells/tissues for rheumatoid arthritis - Wei Xia; Jian Wu; Fei-Yan Deng; Long-Fei Wu; Yong-Hong Zhang; Yu-Fan Guo; Shu-Feng Lei (Immunogenetics, 2017)

iTRAQ-Based Comparative Proteomics Analysis of the Fruiting Dikaryon and the Non-fruiting Monokaryon of Flammulina velutipes - Jing-Yu Liu; Ming-chang Chang; Jun-long Meng; Cui-ping Feng; Yong-nan Liu (Current Microbiology, 2017)

Efficient oxidation of bisphenol A with oxysulfur radicals generated by iron-catalyzed autoxidation of sulfite at circumneutral pH under UV irradiation - Yingtan Yu; Suqi Li; Xinzi Peng; Shaojie Yang; Yifan Zhu; Long Chen; Feng Wu; Gilles Mailhot (Environmental Chemistry Letters, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Erratum to: Influence of climate warming and resin collection on the growth of Masson pine (Pinus massoniana) in a subtropical forest, southern China - Feng Chen; Yu-jiang Yuan; Shu-long Yu; Tong-wen Zhang (Trees, 2016)

MicroRNA let-7g cooperates with interferon/ribavirin to repress hepatitis C virus replication - Wen-Wen Chou; Chung-Feng Huang; Ming-Lun Yeh; Yi-Shan Tsai; Ming-Yen Hsieh; Ching-I Huang; Jee-Fu Huang; Pei-Chien Tsai; Edward Hsi; Suh-Hang Hank Juo; Wei-Lun Tsai; Wan-Long Chuang; et al. (Journal of Molecular Medicine, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Ameliorative Effects of p75NTR-ED-Fc on Axonal Regeneration and Functional Recovery in Spinal Cord-Injured Rats - Yong-Tang Wang; Xiu-Min Lu; Feng Zhu; Peng Huang; Ying Yu; Zai-Yun Long; Ya-Min Wu (Molecular Neurobiology, 2015)

Repair of articular cartilage defects in rabbits through tissue-engineered cartilage constructed with chitosan hydrogel and chondrocytes - Ming Zhao; Zhu Chen; Kang Liu; Yu-qing Wan; Xu-dong Li; Xu-wei Luo; Yi-guang Bai; Ze-long Yang; Gang Feng (Journal of Zhejiang University-SCIENCE B, 2015)

Influence of climate warming and resin collection on the growth of Masson pine (Pinus massoniana) in a subtropical forest, southern China - Feng Chen; Yu-jiang Yuan; Shu-long Yu; Tong-wen Zhang (Trees, 2015)

Rapid field evaluation of the strength of cement-stabilized clayey soil - Zhi-Feng Wang; Shui-Long Shen; Zhen-Yu Yin; Ye-Shuang Xu (Bulletin of Engineering Geology and the Environment, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Sevoflurane-Induced Down-regulation of Hippocampal Oxytocin and Arginine Vasopressin Impairs Juvenile Social Behavioral Abilities - Zhi-Bin Zhou; Xiao-Yu Yang; Bao-Long Yuan; Li-Jun Niu; Xue Zhou; Wen-Qi Huang; Xia Feng; Li-Hua Zhou (Journal of Molecular Neuroscience, 2015)

Sulfide oxidation and nitrate reduction for potential mitigation of H2S in landfills - Yuan Fang; Yao Du; Huan Feng; Li-Fang Hu; Dong-Sheng Shen; Yu-Yang Long (Biodegradation, 2015)

Bioaccessibility and health risk of heavy metals in ash from the incineration of different e-waste residues - Xiao-Qing Tao; Dong-Sheng Shen; Jia-Li Shentu; Yu-Yang Long; Yi-Jian Feng; Chen-Chao Shen (Environmental Science and Pollution Research, 2015)

Birth intervention and non-maternal infant-handling during parturition in a nonhuman primate - Wenshi Pan; Tieliu Gu; Yue Pan; Chunguang Feng; Yu Long; Yi Zhao; Hao Meng; Zuhong Liang; Meng Yao (Primates, 2014)

Change of floral orientation affects pollinator diversity and their relative importance in an alpine plant with generalized pollination system, Geranium refractum (Geraniaceae) - Hui Wang; Chang-Long Xiao; Robert W. Gituru; Zheng Xiong; Dan Yu; You-Hao Guo; Chun-Feng Yang (Plant Ecology, 2014)

Soil fungi rather than bacteria were modified by invasive plants, and that benefited invasive plant growth - Hai Feng Xiao; Yu Long Feng; Douglas A. Schaefer; Xiao Dong Yang (Plant and Soil, 2014)

EPO-Dependent Activation of PI3K/Akt/FoxO3a Signalling Mediates Neuroprotection in In Vitro and In Vivo Models of Parkinson’s Disease - Yu Jia; Shi-Jing Mo; Qi-Qi Feng; Ma-Li Zhan; Li-Si OuYang; Jia-Chang Chen; Yu-Xin Ma; Jia-Jia Wu; Wan-Long Lei (Journal of Molecular Neuroscience, 2014)

Evolutionary increases in defense during a biological invasion - Zhi-Yong Liao; Yu-Long Zheng; Yan-Bao Lei; Yu-Long Feng (Oecologia, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

Incubation of sperm heads impairs fertilization and early embryo development following intracytoplasmic sperm injection (ICSI) by decreasing oocyte activation in mice - Hui Long; Sheng-Sheng Lu; Yan-Ping Kuang; Zhi-Guang Yan; Hong-Xing Liang; Sha Yu; Wei-Ran Chai; Zheng Yan; Qi-Feng Lyu (Biotechnology Letters, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Cloning, expression and characterization of a new ι-carrageenase from marine bacterium, Cellulophaga sp. - Su Ma; Yu-Long Tan; Wen-Gong Yu; Feng Han (Biotechnology Letters, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

High resource capture and use efficiency and prolonged growth season contribute to invasiveness of Eupatorium adenophorum - Wei-Bin Wang; Rui-Fang Wang; Yan-Bao Lei; Chao Liu; Li-Hong Han; Xiao-Dong Shi; Yu-Long Feng (Plant Ecology, 2013)

Molecular cloning and expression of 17β-hydroxysteroid dehydrogenase type 2 gene in Hu sheep - Chang Long Wang; Shi Jia Ying; Zi Yu Wang; Hui Jun Xing; Li Zhong Wang; Dong Yang He; Shen Hua Xiao; Feng Wang (Molecular Biology Reports, 2013)

Temporal and Spatial Expression of KIF3B after Acute Spinal Cord Injury in Adult Rats - Xiaowei Yu; Hai Wen; Jianhua Cao; Binbin Sun; Tao Ding; Ming Li; Hao Wu; Long Long; Xinghai Cheng; Guangfei Xu; Feng Zhang (Journal of Molecular Neuroscience, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population - He Liu; Xia Jiang; Ming-wu Zhang; Yi-feng Pan; Yun-xian Yu; Shan-chun Zhang; Xin-yuan Ma; Qi-long Li; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Synergistic interactions of CO2 enrichment and nitrogen deposition promote growth and ecophysiological advantages of invading Eupatorium adenophorum in Southwest China - Yan-bao Lei; Wei-bin Wang; Yu-long Feng; Yu-long Zheng; He-de Gong (Planta, 2012)

Association mapping for pre-harvest sprouting resistance in white winter wheat - Pawan Kulwal; Goro Ishikawa; David Benscher; Zongyun Feng; Long-Xi Yu; Ashok Jadhav; Subhash Mehetre; Mark E. Sorrells (Theoretical and Applied Genetics, 2012)

Tree ring-based winter temperature reconstruction for Changting, Fujian, subtropical region of Southeast China, since 1850: linkages to the Pacific Ocean - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Tong-wen Zhang (Theoretical and Applied Climatology, 2012)

No evidence for evolutionarily decreased tolerance and increased fitness in invasive Chromolaena odorata: implications for invasiveness and biological control - Yang-Ping Li; Yu-Long Feng; Gregor Barclay (Plant Ecology, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Response of Sulfide:Quinone Oxidoreductase to Sulfide Exposure in the Echiuran Worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Xiao-Li Shi; Ying-Ping Dong; Jin-Long Li (Marine Biotechnology, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

A genetic variant in microRNA-196a2 is associated with increased cancer risk: a meta-analysis - Feng Wang; Yan-Lei Ma; Peng Zhang; Jian-Jun Yang; Hong-Qi Chen; Zhi-Hua Liu; Jia-Yuan Peng; Yu-Kun Zhou; Huan-Long Qin (Molecular Biology Reports, 2012)

Innate and evolutionarily increased advantages of invasive Eupatorium adenophorum over native E. japonicum under ambient and doubled atmospheric CO2 concentrations - Yan Bao Lei; Yu Long Feng; Yu Long Zheng; Rui Fang Wang; He De Gong; Yi Ping Zhang (Biological Invasions, 2011)

Semi-supervised joint spatio-temporal feature selection for P300-based BCI speller - Jinyi Long; Zhenghui Gu; Yuanqing Li; Tianyou Yu; Feng Li; Ming Fu (Cognitive Neurodynamics, 2011)

Study on algorithms of low SNR inversion of T 2 spectrum in NMR - Feng Lin; Zhu-Wen Wang; Jing-Ye Li; Xue-Ang Zhang; Yu-Long Jiang (Applied Geophysics, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Sulfide:quinone Oxidoreductase from Echiuran Worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Zhi Tan; Jin-Long Li (Marine Biotechnology, 2011)

A New Hazardous Solid Waste Detoxication Method: Semi-solid Fenton Process (SSFP) - Li-Fang Hu; Yu-Yang Long; Hua-Jun Feng; Jun Yao; Cheng-Ran Fang; Dong-Sheng Shen (Water, Air, & Soil Pollution, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Growth, biomass allocation, morphology, and photosynthesis of invasive Eupatorium adenophorum and its native congeners grown at four irradiances - Yu-Long Zheng; Yu-Long Feng; Wan-Xue Liu; Zhi-Yong Liao (Plant Ecology, 2009)

Simultaneous detection of human enterovirus 71 and coxsackievirus A16 in clinical specimens by multiplex real-time PCR with an internal amplification control - Xing-Long Xiao; Ya-Qing He; Yi-Gang Yu; Hong Yang; Gu Chen; Hui-Fang Li; Jing-Wei Zhang; Dong-Mei Liu; Xiao-Feng Li; Xiao-Quan Yang; Hui Wu (Archives of Virology, 2009)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

Specific leaf area relates to the differences in leaf construction cost, photosynthesis, nitrogen allocation, and use efficiencies between invasive and noninvasive alien congeners - Yu-Long Feng; Gai-Lan Fu; Yu-Long Zheng (Planta, 2008)

Nitrogen allocation, partitioning and use efficiency in three invasive plant species in comparison with their native congeners - Yu-Long Feng; Gai-Lan Fu (Biological Invasions, 2008)

The combined effects of soil moisture and irradiance on growth, biomass allocation, morphology and photosynthesis in Amomum villosum - Yu-Long Feng; Xin Li (Agroforestry Systems, 2007)

Lipopolysaccharide-induced cerebral inflammatory damage and the therapeutic effect of platelet activating factor receptor antoganist - Wen-Chao Liu; Wen-Long Ding; Hong-Yu Gu; Ming-Feng Chen; Jin-Jia Hu (Neuroscience Bulletin, 2007)

Invasive Buddleja davidii allocates more nitrogen to its photosynthetic machinery than five native woody species - Yu-Long Feng; Harald Auge; Susan K. Ebeling (Oecologia, 2007)

Establishment of a xylose metabolic pathway in an industrial strain of Saccharomyces cerevisiae - Ying Wang; Wen-Long Shi; Xiang-Yong Liu; Yu Shen; Xiao-Ming Bao; Feng-Wu Bai; Yin-Bo Qu (Biotechnology Letters, 2004)